Clinical profile and laboratory parameters of confirmed pediatric scrub typhus cases in a tertiary health care institute - Chadha, Nidhi; Aulakh, Roosy (International Journal of Contemporary Pediatrics, 2023)
Background: Scrub typhus is one of the vector borne tropical infectious disease, caused by O. Tsutsugamushi. Because of nonspecific signs and symptoms and variable prevalence of pathognomic sign (eschar), diagnosis is very difficult in early stage. The purpose of present research was to differentiate that whether case presenting at our institution are different from previously conducted research in various regions. Methods: Hospital record of all reported cases of scrub typhus admitted to department of pediatrics at tertiary health care institute in North India over last two years (2018-2019) was retrieved and reviewed. Results: More cases were reported in male. Maximum number of cases were in 5-10 years i.e. 32 (50.0%) and only one case in less than 12 months. Maximum number cases were reported in August to October 53 (82.8%) as shown. Most common presenting complaint was fever. Most of cases reported with fever of duration of 7-14 days in (51.6%). Rash was present in 7 (10.5%) and eschar in 1 (1.5%). In lab parameters reported abnormalities severe hypoalbuminemia, hyperbilirubinemia, elevated transaminases, anemia, thrombocytopenia leucopenia and leucocytosis. Hepatitis in 48 (75%) was most common complication followed by pneumonia. Other reported complications were myocarditis, acute kidney injury, pneumonia, bleeding, meningitis, enchepalopathy , papilledema, ARDS and hemophagocytosis. Conclusions: Pediatrician should keep high index of suspicion for suspect scrub typhus in a child presents with febrile illness and early treat should be started. Hepatitis is most common complication. As Scrub typhus is associated with multisystem involvement, thorough assessment of patient should be done to look for these complications and appropriate management of complications should be provided to prevent mortality.